New research initiative to address challenges facing Ethiopia’s dairy, poultry and small ruminants’ sectors launched - Gashaw, Tsehay; Haile, Aynalem (CGIAR System Organization, 2022)
Co-creation, with stakeholders, of the SAPLING vision and theory of change for the dairy cattle, poultry and small ruminant value chains in Ethiopia